Dysfunction in Serotonergic and Noradrenergic Systems and Somatic Symptoms in Psychiatric Disorders - Liu, Yi; Zhao, Jingping; Fan, Xiaoduo; Guo, Wenbin (Frontiers in Psychiatry, 2019)
Somatic symptoms include a range of physical experiences, such as pain, muscle tension, body shaking, difficulty in breathing, heart palpitation, blushing, fatigue, and sweating. Somatic symptoms are common in major depressive disorder (MDD), anxiety disorders, and some other psychiatric disorders. However, the etiology of somatic symptoms remains unclear. Somatic symptoms could be a response to emotional distress in patients with those psychiatric conditions. Increasing evidence supports the role of aberrant serotoninergic and noradrenergic neurotransmission in somatic symptoms. The physiological alterations underlying diminished serotonin (5-HT) and norepinephrine (NE) signaling may contribute to impaired signal transduction, reduced 5-HT, or NE release from terminals of presynaptic neurons, and result in alternations in function and/or number of receptors and changes in intracellular signal processing. Multiple resources of data support each of these mechanisms. Animal models have shown physiological responses, similar as somatic symptoms seen in psychiatric patients, after manipulations of 5-HT and NE neurotransmission. Human genetic studies have identified many single-nucleotide polymorphisms risk loci associated with somatic symptoms. Several neuroimaging findings support that somatic symptoms are possibly associated with a state of reduced receptor binding. This narrative literature review was to discuss the involvement of serotonergic and noradrenergic systems in the pathophysiology of somatic symptoms. Future research combining neuroimaging techniques and genetic analysis to further elucidate the biological mechanisms of somatic symptoms and to develop novel treatment strategies is needed.